Analysis of Reward and Career Development on Employee Retention with Job Satisfaction as an Intervening Variable at the PLTU Asam-Asam South Kalimantan - Ashar, Muhammad; Supardi; Sriyono (Jurnal Manajemen, 2025)
This study aims to analyze Rewards and Career Development on Employee Retention and Job Satisfaction of Employees at Asam-Asam PLTU, South Kalimantan. Rewards and career development are important factors in retaining employees and increasing job satisfaction, especially in the electric power industry that demands high skills and loyalty. Literature review shows that rewards, both financial and non-financial, have a positive impact on employee motivation and loyalty. Career development is also considered a key aspect in increasing employee engagement and reducing turnover. The method used in this study is a quantitative method with a survey approach and questionnaire distribution, then the data is processed using the help of smartpls software. The results of this study are rewards, career development, and job satisfaction have a significant influence on employee retention at Asam-Asam PLTU, South Kalimantan. This finding confirms that an effective employee retention strategy must include a combination of fair rewards, career development opportunities, and increased job satisfaction to create a more attractive and supportive work environment.